UTILIZING SURPLUS GEDONG GINCU MANGOES AS CHIPS TO IMPROVE FAMILY ECONOMIES IN JEMBARWANGI VILLAGE - Salas Iqbal Maulana; Nurhaeni Sikki; Hersusetiyati; Pupi Indriati Zaelani; Ratna Deli Sari; Ajeng Nisa Kusuma; Wisnu Wijaya; Cantika Dea Nurlaela Putri; Najmi Ihwani; Ahmad Muzakki (Jurnal Abdisci, 2024)
This community service activity (PKM) was conducted in Jembarwangi Village, Tomo Subdistrict, Sumedang Regency, West Java, known for its cultivation of the exotic Indonesian fruit, Gedong Gincu mango. The village faces significant challenges during the harvest season. When the harvest is abundant, mangoes that do not meet export market criteria (grade Ab1) or local market criteria (grade Ab2) accumulate and rot, potentially harming the environment. To address this issue and boost the local economy, the Community Service Program (KKN) introduced the idea of processing these mangoes into value-added products, namely Gedong Gincu mango chips. However, after the KKN program ended, the activities ceased as the community still required ongoing support. Universitas Sangga Buana YPKP Bandung, supported by the PKM Program from Hibah Bima Dikti 2024, is aiding Jembarwangi Village to market the Gedong Gincu mango chips produced and generate significant profits. The methods used include direct demonstrations of mango chip-making techniques, interactive discussions, and practical training with the local community. The results showed high enthusiasm from the residents, but further support is needed to achieve the desired outcomes. The results of this training are detailed in the article titled "Utilizing Surplus Gedong Gincu Mangoes as Chips to Improve Family Economies in Jembarwangi Village."